Carnivalesque humor, emotional paradoxes, and street protests in Thailand. (February 2016) - Sombatpoonsiri, Janjira
Conventional wisdom has it that street protests are typically driven by rage due to grievances perceived to inflict on a group. This emotive atmosphere can shape protest methods to be vandalistic to the point where armed attacks against targeted opponents are justified. This paper suggests that rage-influenced struggle can be counterproductive as it obstructs a movement from building a coalition board enough to challenge the ruling elites it opposes. This paper argues that carnivalization of protests can prevent this setback in two directions. First, it potentially transforms protesters' collective emotion from rage to cheerfulness. This effect may lessen a possibility where protesters project violent revenge on those thought to represent the ruling elites. Second, while helping protesters to address sources of their grievances, carnivalesque protests create a "friendly" image that may convince a public audience outside the movement to support its cause. In assessing a political process of carnivalesque protests, this paper bases its analysis on an account of protest actions by Thailand's Red Sunday group emerging after the 2010 crackdown.